All Possible Worlds: A History of Geographical Ideas - Martin, Geoffrey J. (Oxford University Press, 2005)
Keywords: Geography; History; dept.egm

The Kyrgyz Republic's Liminal Media: assessing a journalistic rite of passage - Manzella, Joseph C; Yacher, Leon (Journalism Studies, 2005)
In the Western world, the Kyrgyz Republic has been depicted as a democratic success story. Indeed, unlike other Central Asia nation states, the Kyrgyz media appears on the surface relatively free. This paper examines the Kyrgyz press in the context of journalistic ideologies, and suggests that the republic's media is going through an important transitional phase, the central stage of a journalistic rite of passage. Part of that transitional process is an ongoing ideological tug-of-war that awaits resolution. It is suggested that such resolution may occur only when the press becomes economically self-sustaining. © 2005 Taylor & Francis Group, LLC.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-223-242-778-009 tex.type: [object Object]
Keywords: Journalistic Ideologies; Kyrgyz Media; Rite of Passage; dept.egm